2023
DOI: 10.1186/s12876-023-02652-3
|View full text |Cite
|
Sign up to set email alerts
|

The impact of intrahepatic cholestasis on pregnancy outcomes: a retrospective cohort study

Abstract: Background This study analyzed the pregnancy outcomes of patients with intrahepatic cholestasis of pregnancy (ICP) in Hangzhou, China. Methods Cases of pregnant women monitored by antepartum testing at Hangzhou Women’s Hospital from January 2018 to December 2020 were reviewed. Subjects were classified into two groups according to whether they had ICP: 688 cases of ICP were assigned to an exposure group while 38,556 cases of non-ICP were assigned to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 44 publications
1
10
0
1
Order By: Relevance
“…A cohort study of 39,742 pregnant women showed that maternal age younger than 25 years or older than 35 years, low or high prepregnancy body mass index (BMI), being positive for hepatitis B surface antigen, multiple pregnancies, low maternal education level, insufficient pregnancy weight gain, in vitro fertilization, history of cesarean delivery, or history of two or more miscarriages were all associated with an increased risk of ICP 7 . In addition to these factors, a retrospective study of 39,244 pregnant women found that those with gestational hypertension, preeclampsia, thrombocytopenia, hyperlipidemia, and gestational diabetes mellitus (GDM) had a higher risk of ICP than others 8 . Among the ICP patients, those with GDM, a history of ICP, previous cholecystectomy, and smoking history were more likely to develop severe ICP (TBA concentration, >100 μmol/L) 9 .…”
Section: Clinical Question 1: What Are the High-risk Factors Associat...mentioning
confidence: 99%
“…A cohort study of 39,742 pregnant women showed that maternal age younger than 25 years or older than 35 years, low or high prepregnancy body mass index (BMI), being positive for hepatitis B surface antigen, multiple pregnancies, low maternal education level, insufficient pregnancy weight gain, in vitro fertilization, history of cesarean delivery, or history of two or more miscarriages were all associated with an increased risk of ICP 7 . In addition to these factors, a retrospective study of 39,244 pregnant women found that those with gestational hypertension, preeclampsia, thrombocytopenia, hyperlipidemia, and gestational diabetes mellitus (GDM) had a higher risk of ICP than others 8 . Among the ICP patients, those with GDM, a history of ICP, previous cholecystectomy, and smoking history were more likely to develop severe ICP (TBA concentration, >100 μmol/L) 9 .…”
Section: Clinical Question 1: What Are the High-risk Factors Associat...mentioning
confidence: 99%
“…Chen et al found that patients with ICP had increased risk of preterm birth and low birth weight, as well as a higher CS ratio. 6 A meta-analysis also showed the increased risk of preterm birth, iatrogenic preterm birth, meconium-stained amniotic fluid, and NICU admission in the ICP group compared with the control group. The risk of stillbirth was significantly higher in women with ICP when serum bile acid concentrations were ≥100 μmol/L.…”
Section: Discussionmentioning
confidence: 97%
“…Unfavorable perinatal outcomes related to ICP have been demonstrated in many studies. Chen et al found that patients with ICP had increased risk of preterm birth and low birth weight, as well as a higher CS ratio 6 . A meta‐analysis also showed the increased risk of preterm birth, iatrogenic preterm birth, meconium‐stained amniotic fluid, and NICU admission in the ICP group compared with the control group.…”
Section: Discussionmentioning
confidence: 99%
“…This study focused on the role of dyslipidemia in abnormal pathophysiologic processes. Research by Chen Y et al demonstrated a higher prevalence of hyperlipidemia in individuals with ICP compared to those without (5.96% vs. 3.80%), identifying ICP as an independent risk factor for dyslipidemia ( 35 ). Building on this, our study employed mediator MR analysis to substantiate the significant indirect effect of ICP on CVD via lipid levels.…”
Section: Discussionmentioning
confidence: 99%